Diffusion NMR: From catalysts to gelatin, a useful tool for exploring structure and dynamics in porous networks - D’Agostino, Carmine (Diffusion Fundamentals, 2017)
In this work several applications of the technique to systems of industrial relevance, including catalysts and gelatinous materials, will be presented.